A Child with Lymphangioma of Tongue Treated with Constitutional Homoeopathy Medicine—A Rare Case Report - Parveen, Suraia; Ali, SK Mahasin (Homœopathic Links, 2021)
Lymphangiomas are rare benign hamartoma tumours resulting from a congenital malformation of the lymphatic system that are commonly seen in the head and neck region and are rare in the oral cavity. In intraoral lymphangioma, the tongue is the most affected site and shows multiple blister-like nodules with red or purple translucent vesicles on the anterior two-third of ventral and dorsal surface of tongue. Patients with lymphangioma of tongue are associated with difficulties in feeding and mastication, speech disturbances, bleeding from tongue surface, burning sensation of tongue, poor oral hygiene, dental problem and macroglossia. They are usually diagnosed in infancy and early childhood. In conventional method, surgical excision is the treatment of choice but recurrences and postoperative complications are common. Here, we present one such rare case of intraoral lymphangioma involving the tongue of a 4 years old male child who was successfully treated with constitutional homoeopathic medicine Tuberculinum.
Keywords: lymphangioma; tongue; homoeopathy; Tuberculinum